Pengaruh Lokasi Terhadap Kenyamanan Berkunjungnya Konsumen Dengan Menggunakan Program Statistical Program For Social Science (SPSS) Pada (Studi Kasus : Cafe XY - Fitriyani, Resty (Jurnal Ilmiah Wahana Pendidikan, 2026)
In Indonesia, teachers' ability to undertake research is still below average. This study aims to determine the effect of Location on the Convenience of Visiting Consumers. The population taken is consumers who have visited with a sample of 54 respondents. The results showed that there was an influence between location and convenience. This was obtained through the T test with a tcount value of 0.000 and a significance value of 0.05, and a coefficient of determination of 0.718 which means that 71.8% and the remaining